Budgetary Policy of Ukraine in the Sphere of Expenditure as a Basis for Prospective Economic Development - O. Cheberyako; O. Klekota (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The main trends of budgetary policy in the sphere of expenditures are investigated as a basic condition for improvement of the system of management of budgetary expenditures. The structure of budget expenditures at different levels and the main directions of using budget expenditures are analyzed. The main measures of the state policy of Ukraine in the sphere of expenditures are revealed, depending on the cooperation with the IMF, as well as the proposals on amendments to the normative-legal acts of Ukraine in the field of program-target method and budget planning. General scientific and special methods of research, methods of grouping, classification and graphical representation of the achieved results are used. The information base of the research is the normative and legislative acts that regulate the financial policy of the state and, at the same time, the budgetary policy; monographs and articles of domestic and foreign economists in professional economic publications; materials of scientific conferences and seminars on budget policy.